PENGARUH MODEL COOPERATIVE LEARNING TYPE MAKE A MATCH TERHADAP MINAT BELAJAR PERKALIAN PADA PEMBELAJARAN MATEMATIKA SISWA SD - Sartika, Ratmi; Rury Rizhardi; Noviati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the Effect of the Cooperative Learning Type Make A Match Model on the Interest in Learning Multiplication in Elementary School Students' Mathematics Learning. The background of this study is the low interest of students in learning multiplication material which has an impact on mathematics learning outcomes. The method used in this study is a Quasi Experiment with a Nonequivalent Control Group Design. The subjects of the study were class II at Elementary School 141 Palembang, which consisted of an experimental class and a control class. The experimental class used the Cooperative Learning Type Make A Match model, while the control class used conventional learning. Data collection techniques were carried out through observation, learning interest questionnaires, and documentation. Data were analyzed using the T-test. The results showed that there was a significant difference between students' learning interests using the Cooperative Learning Type Make A Match model compared to students who used conventional learning. Thus, the Cooperative Learning Type Make A Match model has a positive effect on increasing students' interest in learning multiplication. This model is recommended to be applied as an alternative mathematics learning strategy in Elementary Schools.